Penyatuan mata wang sebagai strategi peningkatan kuasa ekonomi negara Islam (Monetary Union as a strategy to uplift economic power of Islamic Nations) - Sanep Ahmad; Dwi Condro Triono (Institut Kajian Rantau Asia Barat, 2011)
There have been suggestions that Gold Dinar be used again as a currency among the Islamic countries for the purpose of elevating the Islamic currency. Furthermore, it is also for reducing the dependency of the Islamic countries on the US Dollar. The question to ponder is: can monetary union be implementd simultaneously through out all the Islamic countries? Besides, the reusing of Gold Dinar needs monetary transformation within the Islamic countries. How the monetary transformation should be executed such that it produces the best effect to all Islamic countries ? This study aims to investigate the appropriateness of currency union among Islamic West Asian Countries as a strategy for economic cooperation for increasing the economic power of Islamic countries. The study uses data of selected Islamic West Asian Countries for 30 years and analysed based on OCA theory using SVAR model. The finding showed that it is not appropriate to perform the currency union simultaneously in all Islamic West Asian Countries. Currency union among Islamic West Asian Countries could only be done in stages according to zones. The study concluded that curency union among Islamic West Asian Countries is not appropriate to become a strategy for the purpose of increasing the economic power of Islamic countries worldwide. Monetary union among the Islamic countries should be implemented in stages beginning from smaller zone for to achieve the best effect.